Evaluación de cambio en psicoterapia con niños institucionalizados (2018)
ABSTARCT: The objective of the research was to evaluate the change in the psychological difficulties of institutionalized children who received psychotherapeutic treatment for four months. It was a collective case study with a intra and inter-caso analysis. In this study the data of four therapies were used. A pre and post-therapy clinical evaluation was carried out and it was triangulated with the participants' perception about the therapeutic changes. The participants were children of school age, their parents and the psychotherapists in charge. In the results, the emotional dimension stood out as an area of common affectation and positive change in the cases studied, although there was variation in the problematized psychological areas case by case, a decrease in the chronicity of reported difficulties was observed and positive change in the patient's perception about the interference of their problems in daily life. The support and willingness of the parents were an influential factor in the effectiveness of the psychotherapy.